Occurrence of Derxia sp. in some Brazilian soils - Campêlo, Adalis Bezerra; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
Derxia occurrence was studied in 100 soil samples collected in the states of São Paulo, Rio de Janeiro, Pernambuco and Pará. Soil bacteria were isolated on a nitrogen free agar media containing starch as a carbon source and added sodium bicarbonate. Plates were inoculated by placing bits of root material or soil granules directly on the surface of the media. The bacteria was found in soils from the states of Pará and Rio de Janeiro but not in the dry soils of São Paulo and Pernambuco. Of the total number of soil samples 36% were positive. Soil humidity apparently favored Derxia development, 77% of the flooded soils, 36% of the humid soils and only 13% of the dry collected soils contained the bacteria. Its occurrence appeared to be more frequent on plates inoculated by roots (33%) than on those inoculated with portions (26%). Derxia sp. was found in soils of a pH range between pH 4.5 and 6.5, the largest occurrence being observed between pH 5.1 and 5.5.